Assessment of titanium - tungsten iron oxide and their gas sensor application - Turgut, Erdal; Şenarslan, Elvan; Muğlu, Günay Merhan; Saritas, Sevda (Physics and Chemistry of Solid State, 2024)
TixFe3-xO4 and WxFe3-xO4 structures were grown. When examining the atomic percentages of the films grown under the same conditions as the EDX measurements, different ratios are observed in the WxFe3-xO4 structure (O: 71.05%, Fe: 4.22%, W: 24.74%). This is the opposite in the structure of TixFe3-xO4 (O; 58.16%, Fe; 41.68%, Ti; 0.17%). It is possible to say that the power source has an effect here, but also plasma thermodynamics and activation energies of metals play a significant role. The difference in the amount of oxygen in the structures is quite evident. The band gap energy of the as-grown and annealing TixFe3-xO4 structures were determined to be 2.19 eV and 2.14 eV respectively from absorption data. As grown and annealing WxFe3-xO4 structures were determined to be 3.09 eV and 3.15 eV respectively. The response of WxFe3-xO4 structure to hydrogen gas was measured at flow values of 1000 ppm, at 300 degrees, under white light and dark for 300, 180, and 120 seconds, and it has been seen that the examined thin films are suitable for gas sensor application under white light. The WxFe3-xO4 structure exhibits light sensitivity, despite having a relatively wide band gap. However, there is no evidence to suggest that this sensitivity is caused by hydrogen gas; but, it can be said it is sensitive to light. Also, the response of the TixFe3-xO4 structure was measured for 600 seconds, and it has been seen that the examined thin films are not suitable for gas sensor application under white light.